Plasma Lipid Profile and Intestinal Microflora in Pregnancy Women With Hypothyroidism and Their Correlation With Pregnancy Outcomes - Cai, Yanjun; Xu, Yajuan; Ban, Yanjie; Li, Jingjing; Sun, Zongzong; Zhang, Miao; Wang, Biao; Hou, Xiaofeng; Hao, Yingqi; Ouyang, Qian; Wu, Bo; Wang, Mengqi; et al. (Frontiers in Endocrinology, 2022)
Objective: To investigate the lipid profiles and intestinal microflora in pregnant patients with hypothyroidism and their correlation with pregnancy outcomes. Methods: In total, 27 pregnant women with hypothyroidism (study case) and 28 normal pregnant women (control group) were enrolled in this study. The lipid profiles and intestinal microflora in the two groups were compared using untargeted liquid chromatography-mass spectrometry (LC-MS) and 16S rRNA amplicon sequencing, respectively. The association among the differential metabolites, intestinal microflora, serological indicators and pregnancy outcomes was further analyzed. Results: Patients in study case had higher C-reactive protein (CRP) levels (P = 0.025) and lower birth weight (P=0.005) than the control group. A total of 42 differential lipid metabolites and 7 enrichment KEGG pathways were obtained between the two groups (VIP ≥ 1，P < 0.05). Ten lipid metabolites can be used as characteristic metabolites of study case, including phosphatidylcholine (PC), phosphatidylethanolamine (PE) and sphingomyelin (SM). The richness and diversity of intestinal microflora in study case were lower than those in the control group (P＞0.05). LEfSe analysis revealed that patients in study case had higher abundance of Prevotella and Haemophilus and lower abundance of Blautia than the control group (P < 0.05). Blautia was positively correlated with SM and negatively correlated with PC and PE; the CRP level and Prevotella were positively correlated; the neonatal weight and PC level were negatively correlated (P < 0.05). Conclusion: The lipid profile and intestinal microflora of pregnant women with hypothyroidism significantly differed from those of normal pregnant women and were associated with adverse pregnancy outcomes. The interaction between lipid metabolism and intestinal microflora may be a potential target for further studies investigating the pathogenesis of hypothyroidism during pregnancy.